Escala de avaliação discente do ensino emergencial: construção e análise - Tischer, Jacson Hordy (2022)
The extraordinary circumstances resulting from the pandemic period with the closure of almost all higher education institutions, in addition to the mandatory institutional assessments defined by law, and the importance of obtaining data on the quality of teaching methods, led universities to seek instruments which measured the educational capacity of emergency teaching. Therefore, this study sought subsidies that would consolidate the creation of a model which would evaluate the emergency education, in a summarized way, covering the requirements of the law and complying the legal steps that weigh up on student evaluation. In this way, an instrument of evaluation was proposed by higher education institutions by the view of students in an emergency teaching situation. The study followed the methodological propositions of Boateng et al. (2018), which defines and establishes the good practices in the development of scales, and was divided into three phases. The first one, qualitative nature, instrument's items were raised and evaluated, being identified in the literature for the Teacher, Teaching and Discipline dimensions, which were initially believed to be the factors that would compose the self-assessment. The second phase, the research became a survey, evaluating 4920 disciplines, by the students of 239 higher education courses at Federal University of Santa Maria. Data analysis, using descriptive statistics, showed that students are quite satisfied with the effort, involvement, availability and skills of the teacher during the pandemic period. As they also think that synchronous classes contributed to learning, and the proposed activities were befitting with the level of difficulty of the contents presented. In addition, they evaluated positively the sequence of disciplines in the course, understanding their relevance and representativeness in training and professional life.The third stage of the study, exploratory factor analysis techniques, confirmatory factorial and structural equation modeling were used. During the proposition of the model through tests that sought to analyze the reliability and validity of the dimensions, the Teaching factor did not reach validity discriminant and demonstrated unsatisfactory coefficients, resulting in the grouping to the Teacher dimension. For the new proposed model, the Professor dimension had greater overall weight, and the items which deal with satisfaction with the course and the relevance of disciplines in student training were the most significant in the overall evaluation. It is pertinent to expose that, through comparing competing models, the created scale demonstrated to be more parsimonious in relation to the one-dimensional hypothetical model. The research ended with the development of a methodology for the application of the student evaluation scale for emergency teaching which will be able to be used in a simplified way by any researcher, agent or manager of the institutions, or even any interested one.